Evaluation of Toxicological Effects of Brown Seaweeds: Part I. - ISMAIL, SHAHNAZ; MIRZA , MARY AM; QURESHI, SHAMIM; BADAR, YASMEEN (Biological Sciences - PJSIR, 2022)
For determining moisture and ash [17], one gram sample of each seaweed was kept in oven at 110°C for 6 hr. Cooled in desicator to constant weight. Finally moisture was calculated. The toxicity of Cystoseira barbata, Padina pavonia and Sargassum boveanum was determined by the administration of dried powder via oral route [18] in normal albino mice,